New records of coprophilous ascomycetes in the Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
There are presented new records of coprophilous Ascomycota representatives collected in the Crimea in 2008–2009. Characters of their morphology, ecology, taxonomy and localities in Ukraine are discussed. Delitschia marchalii Berl. et Vogl. in Sacc., Lasiobolus intermedius J.L.Bezerra et Kimbr., Phomatospora minutissima (P. Crouan et H. Crouan) N. Lundq., Podospora australis (Speg.) Niessl, P. communis (Speg.) Niessl, Saccobolus minimus Velen., Sordaria superba De Not., Sporormiella dubia S.I. Ahmed et Cain та Zygopleurage zygospora (Speg.) Boedijn. are first recorded in Ukraine. Descriptions, illustrations, synonyms and general distribution are provided for such species. Rare species Ascobolus albidus P. Crouan et H. Crouan, Coprotus luteus Kimbr., Podospora decipiens (G. Winter ex Fuckel) Niessl, Saccobolus truncatus Velen., Schizothecium vesticola (Berk. et Broome) Lundq.and Trichobolus sphaerosporus Kimbr. have been also revealed.
Keywords: Ascomycota, coprophilous fungi, Crimea, Ukraine.